2020
DOI: 10.1002/tax.12209
|View full text |Cite
|
Sign up to set email alerts
|

New insights into biogeographical disjunctions between Taiwan and the Eastern Himalayas: The case of Prinsepia (Rosaceae)

Abstract: To understand better the mechanisms underlying the disjunct distribution of plants between Taiwan and Himalayasouthwestern China, the genus Prinsepia (Rosaceae) was examined using phylogenetic and dating approaches based on molecular evidence. Prinsepia comprises four allopatric species with distributions in four subregions of China, i.e., P. scandens (southeastern China: Taiwan), P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
(76 reference statements)
1
5
0
Order By: Relevance
“…The disjunctive distribution pattern between the Himalayas and Taiwan has been observed in species within this genus, such as P. microstomum and P. shevokii , although the biogeographical history underlying this pattern remains unexplored [ 4 , 11 ]. This pattern of disjunction aligns with the biogeographical narratives derived from the phylogenetic and molecular dating studies of vascular plants, which have posited the Himalayas as an origin point for the genera Theligonum , Kelloggia , Triplostegia , and Prinsepia [ 12 , 13 , 14 ].…”
Section: Introductionsupporting
confidence: 72%
“…The disjunctive distribution pattern between the Himalayas and Taiwan has been observed in species within this genus, such as P. microstomum and P. shevokii , although the biogeographical history underlying this pattern remains unexplored [ 4 , 11 ]. This pattern of disjunction aligns with the biogeographical narratives derived from the phylogenetic and molecular dating studies of vascular plants, which have posited the Himalayas as an origin point for the genera Theligonum , Kelloggia , Triplostegia , and Prinsepia [ 12 , 13 , 14 ].…”
Section: Introductionsupporting
confidence: 72%
“…Although these two regions are not adjacent or even far apart, they have similar plant community compositions. Many different types of plants are distributed in these two regions but not in the southern region of China, which is located between these two regions, presenting a geographically disjunct distribution pattern (Chen et al., 2013; Jin et al., 2020). The high‐elevation area from 1550 m to 2350 m has the greatest concentration of taxa with disjunct distributions between southwestern China and Taiwan Island.…”
Section: Introductionmentioning
confidence: 99%
“…Biogeographic disjunctions between mainland China-Taiwan island have received considerable attention with the separation of the two regions by 130 km (Wu and Wang, 2001; Xiang and Soltis, 2001; Qiu et al, 2011; Chen et al, 2012; Ye et al, 2014, Jin et al, 2020). The island of Taiwan is the largest subtropical mountainous island in the monsoonal western Pacific region, located on the Tropic of Cancer, and originated in the late Miocene (ca.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular phylogenetic analyses have shown that several plant lineages have disjunct distributions between mainland China and Taiwan (e.g., Sassafras J. Presl, Nie et al, 2007; Pseudotsuga Carrière, Wei et al, 2010; Triplostegia Wall. ex DC., Niu et al, 2018; Prinsepia ., Jin et al, 2020). Geologically, the island of Taiwan and its adjacent continental margin of mainland China belong to the Eurasian plate; in the Late Cretaceous both were part of the continental block.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation